2002
DOI: 10.1093/jn/132.5.901
|View full text |Cite
|
Sign up to set email alerts
|

Early Posthatch Starvation Induces Myonuclear Apoptosis in Chickens

Abstract: The effect of early posthatch starvation on myonuclear apoptosis was examined in chickens. Male broiler chickens were or were not provided feed for the first 3-d posthatch. Subsequently, all chickens were provided feed for an additional 4-d posthatch. Chickens were killed at 3- and 7-d posthatch, and the pectoralis thoracicus was harvested, fixed and embedded in paraffin. Muscle sections were labeled with the terminal deoxynucleotidyl transferase histochemical staining technique to identify apoptotic nuclei. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 17 publications
2
18
0
2
Order By: Relevance
“…These myoblasts subsequently fuse with other myoblasts, as well as damaged muscle fibers, to form new functional muscle. This process may be particularly vulnerable to postnatal nutrition, as starvation reduces satellite cell proliferation and increases apoptosis in poultry [15][16][17] and satellite cell number is reduced in malnourished human children [18]. Reduced function of genes critical for postnatal satellite cell survival, such as Pax7, can cause accelerated muscle wasting soon after birth [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These myoblasts subsequently fuse with other myoblasts, as well as damaged muscle fibers, to form new functional muscle. This process may be particularly vulnerable to postnatal nutrition, as starvation reduces satellite cell proliferation and increases apoptosis in poultry [15][16][17] and satellite cell number is reduced in malnourished human children [18]. Reduced function of genes critical for postnatal satellite cell survival, such as Pax7, can cause accelerated muscle wasting soon after birth [14].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, satellite cells appear to be particularly sensitive to nutritional availability during periods of high growth. In poultry, early postnatal starvation yields reduced satellite cell proliferation, increased apoptosis, and sustained reductions in muscle mass despite normalization of food intake [15][16][17]. Reduced satellite cell number has also been observed in malnourished human children [18].…”
Section: Introductionmentioning
confidence: 99%
“…Mozdziak et al [13] suggested in their study that a delay in the access to feed (a 72-h fasting period) induced a greater percentage of nuclear apoptosis in muscle cells when compared with samples from birds that had access to feed immediately after hatching. This greater degree of cell damage was translated into smaller sized muscle fibers and a subsequently lower BW.…”
Section: Description Of Problemmentioning
confidence: 98%
“…Cells isolated from both muscles of callipyge individuals were more resistant to apoptosis induced by serum deprivation than cells isolated from corresponding muscles of normal individuals. Apoptosis is known to be important in regulating the development of many tissues by removing unwanted cells, and has been linked to terminal myogenic differentiation and skeletal muscle atrophy associ- ated with disuse, starvation and diseases such as Duchenne muscular dystrophy [Allen et al, 1997;Tews and Goebel, 1997;Sandri et al, 1998;Mozdziak et al, 2002]. Furthermore, peptide growth factors such as myostatin and insulin-like growth factor-I, which are known to regulate muscle mass in vivo, directly affect myoblast apoptosis in vitro [Napier et al, 1999;Rios et al, 2001].…”
Section: Discussionmentioning
confidence: 99%